Microorganism Based Biopolymer Materials for Packaging Applications: A Review - Brodnjak, Urška Vrabic (Journal of Composites and Biodegradable Polymers, 2016)
Polymers which are produced naturally or genetically from microorganisms, have a great potential in many fields of material science. One of them are coatings and films which can also be used in packaging materials (papers, boards, cardboards). Polymers like bacterial cellulose, Xanthan, Curdlan and Pullulan are polymers, produced from different bacteria, with specific properties. This group of polymers consists mainly from polyhydroxyalkanoates. Hyaluronic Acid, Poly (gamma-glutamic acid), Cyanophycin and Microbial Exopolysaccharides are well known polymers, but not commonly used in packaging field. Their applications are promising but still under research and implementation. One of the main drivers and the goal for the development of bio based coatings from different bio based polymers, is the production of materials which are fully biodegradable, made from the renewable raw materials. Fermentation of agricultural products produced by bacterial microorganisms causes the production of polymers as substrates. The applications of this products could lead to new possibilities for improving base materials, substrates such as papers, boards and cardboards. The applicability into the coating industry is still related with performance, processing and costs of such polymers. The review paper introduces new possibilities of polymers made from microorganisms, which have a potential in a coating industry.